Foreign direct investment and economic growth nexus in ECOWAS: The leveraging effect of anti-corruption - Grace Nkansa Asante; Kofi Kamasa; Myles Patrick Bartlett (Economic Journal of Emerging Markets, 2022)
Purpose ― This paper sought to investigate the interactive effect of corruption and FDI on economic growth in the Economic Community of West African States (ECOWAS) region empirically. Methods ― With panel data spanning 2000–2019 across 15 ECOWAS countries, this paper estimates its results by employing the system-GMM estimator, which combines a system of regressions in difference and in levels to resolve the problem of endogeneity. Findings ― Results reveal that while FDI independently spurs economic growth, control of corruption has no direct effect on growth in the region. The interactive effects reveal the complementarity between FDI and control of corruption in promoting economic growth in the ECOWAS region. The growth effect of FDI is larger and stronger given an improvement in the control of corruption across the 1st, 5th, 10th, and 25th percentiles. Implication ― To improve investor confidence, bolster FDI inflows and optimize its beneficial impacts on economic growth, this paper calls for measures to increase transparency and stronger political commitment to strictly investigate, prosecute and punish corruption in the ECOWAS region. Originality/value ― Although foreign direct investment (FDI) to host countries have been shown in the literature to be a crucial driver of economic growth, little is known about how anti-corruption measures affect the FDI-growth relationship. This paper contributes to policy by providing empirical evidence to bridge this gap.